2016
DOI: 10.1103/physrevlett.117.147203
|View full text |Cite
|
Sign up to set email alerts
|

Hot-Electron-Induced Ultrafast Demagnetization inCo/PtMultilayers

Abstract: Using specially engineered structures to tailor the optical absorption in a metallic multilayer, we analyze the magnetization dynamics of a Co/Pt multilayer buried below a thick Cu layer. We demonstrate that hot electrons alone can very efficiently induce ultrafast demagnetization. Simulations based on hot electron ballistic transport implemented within a microscopic model that accounts for local dissipation of angular momentum nicely reproduce the experimental results, ruling out contribution of pure thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
122
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(138 citation statements)
references
References 39 publications
10
122
1
1
Order By: Relevance
“…These hot electrons are shown to travel into the Cu layer before interacting with the magnetization of the [Co/Pt] multilayer. It is then demonstrated that hot electrons alone can very efficiently induce ultrafast demagnetization [123]. More importantly, simulations based on hot electron ballistic transport, implemented within a microscopic model that accounts for the local dissipation of angular momentum, nicely reproduce the experimental results, ruling out the contribution of pure thermal transport [123].…”
Section: Institut Jean Lamour Umr 7198 Cnrs -Université De Lorrainementioning
confidence: 59%
See 1 more Smart Citation
“…These hot electrons are shown to travel into the Cu layer before interacting with the magnetization of the [Co/Pt] multilayer. It is then demonstrated that hot electrons alone can very efficiently induce ultrafast demagnetization [123]. More importantly, simulations based on hot electron ballistic transport, implemented within a microscopic model that accounts for the local dissipation of angular momentum, nicely reproduce the experimental results, ruling out the contribution of pure thermal transport [123].…”
Section: Institut Jean Lamour Umr 7198 Cnrs -Université De Lorrainementioning
confidence: 59%
“…It is then demonstrated that hot electrons alone can very efficiently induce ultrafast demagnetization [123]. More importantly, simulations based on hot electron ballistic transport, implemented within a microscopic model that accounts for the local dissipation of angular momentum, nicely reproduce the experimental results, ruling out the contribution of pure thermal transport [123]. Moreover, by replacing the [Co/Pt] layer by a GdFeCo layer, GdFeCo magnetization switching using ultrafast hot electron pulses and without direct light interaction was demonstrated [124].…”
Section: Institut Jean Lamour Umr 7198 Cnrs -Université De Lorrainementioning
confidence: 99%
“…Recently, photo‐induced spin dynamics has been extensively investigated since Beaurepaire et al first reported an ultrafast demagnetization by femtosecond laser pulse in ferromagnetic Ni film by means of time‐resolved magneto‐optical Kerr effect (TR‐MOKE) measurement . Several mechanisms, such as electron–magnon interaction, Coulomb interaction, electron–phonon scattering, effect of magnetic domain, direct angular momentum transfer, hot‐electron‐induced demagnetization, and superdiffusive spin current, have been proposed to explain the ultrafast demagnetization phenomenon. The exact underlying physics of the ultrafast spin dynamics is still under intense debate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since Malinowski 17 et al first proposed that the laser excited spin current transport could increase and speed up the magnetic quenching in metallic heterostructures, the laser-induced super-diffusive spin current was raised to play an important role in determining the ultrafast demagnetization in metallic films or heterostructures [18][19][20][21][22] . However, the recent demonstration 23 shows that the unpolarized hot electrons transport can 4 demagnetize a ferromagnet, indicating the local spin angular momentum dissipation is unavoidable even when super-diffusive spin transport domains in the metallic heterostructures. Moreover, even in the similar samples, the local spin-flip scattering and nonlocal spin transport mechanism were proposed respectively by different experimental tools 19,24 to explain the ultrafast demagnetization.…”
mentioning
confidence: 99%
“…It is harmful for clarifying the underlying ultrafast demagnetization mechanism in such metallic heterostructures. Therefore, an effective method to distinguish the two dominant contributions to ultrafast demagnetization in metallic heterostructures is highly desirable 19,23,24 . Here, we propose that investigating both the ultrafast demagnetization time and Gilbert damping 25 simultaneously is a candidate method, although the relationship between the two parameters has never been unified successfully so far between the experiments and theoretical predictions.…”
mentioning
confidence: 99%